Prayer Time Calculation Using Approximated Epimeris Data - Handhita, Emye Tegar (University of Muhammadiyah Sumatera Utara, 2023)
Prayer time can be determined by observing sun movement, and can also be determined by mathematical calculation. Determining prayer time by mathematic calculation needs input in form of ephemeris data. Ephemeris data can be obtained from table such as using winhisab application. Other than that ephemeris data can also be obtained by mathematic calculation with approximation method. The data calculated with approximation method is not exactly the same as data obtained from winhisab, however the difference is not that great. Prayer time schedule calculated with approximated data should not be that much different from the one calculated with the data from winhisab.Keyword: Prayer Time, Approximation, Ephemeris, Winhisab